Rural roads maintenance at Kampung Tepi Alor, Mukim Naga, Kedah / Rashdan Munir Badrul - Badrul, Rashdan Munir (Universiti Teknologi MARA UiTM,Perak, 2022)
Industrial training is an important course for students in certain programs at all levels of higher education. The purpose of industrial training is to expose the students to the real industry after graduates and give opportunities in the workplace to receive practical experience to improve the skills.This course provides exposure and experience to the students in terms of technology development, effective communications, teamwork practices, policies, procedures and regulations, professional perspectives, and reporting. This course will build enthusiasm and proactive attitude among students and increase their confidence to practice professional ethics in work.